MANAGEMENT PROTOCOL FOR PATIENTS WITH JUVENILE ARTHRITIS - A. A. Baranov; E. I. Alexeeva; T. M. Bzarova; S. I. Valieva; R. V. Denisova; K. B. Isaeva; P. F. Litvitskii; E. V. Mitenko; T. V. Sleptsova; A. N. Fetisova; E. G. Chistyakova; N. I. Taibulatov; et al. (Вопросы современной педиатрии)
Management protocol for patients with juvenile arthritis was developed with the assistance of the workers from the two largest educational scientific research institutions — Scientific Centre of Children Health and I.M. Sechenov First Moscow Medical State University. The authors summarized international and their own long-term clinical experience and showed the modern data on etiology, pathogenesis, diagnostics and treatment of juvenile arthritis.